Estudo de comunidades de dípteros necrófagos sob o formalismo de biclusters e árvores de decisão - Souza, Caroline Rodrigues de [UNESP] (2016)
The pattern recognition in ecological communities is one of the most antique and persistent challenges of ecological science. In this sense, through mathematical modelling from graphs, using biclusters and decision trees, the objective of the present work was to find patterns in the occurrence of necrophagous dipterans collected in three different areas (rural, urban and forest) and with three different baits (sardines, liver and beef) in the city of Rio Claro-SP. Algorithms (InClose and RInClose-biclusters, C 4.5-decision trees) were used to obtain the results. Through the analysis of biclusters, it can be highlighted those that related Atherigona orientalis (Schiner) and Musca domestica Linnaeus in all environments, less forest area, probably due to the fact of being species known for their preference for areas inhabited by humans. On the other hand, even being species possessing high dependence by antropobiocenose, other biclusters indicated an association between Lucilia eximia (Wiedemann) and Chrysomya megacephala (Fabricius) occurring with greater frequency in the forest, attracted by the bait of meat or liver, both known for their importance in the attractiveness of calliphorid fly. This may be explained due to the population growth occurred around the forest, giving the characteristics of place inhabited by man. With regard to decision trees, were obtained in total 19 decision trees (8 to the family Sarcophagidae, 4 for Muscidade and 7 to Calliphoridae) and from them various patterns can be detected such as: A. orientalis, Synthesiomyia nudiseta (Wulp, 1883) and M. domestica being present together if the season is Spring, the bait is sardines and the location is urban. Oxysarcodexia thornax (Walker) was the only specie in which to achieve the condition of presence, it is necessary to walk only one node (the spring), therefore, it was considered to be generalist in this study, since the local variables and bait were indifferent to determine this location. For all that, it was considered that the decision trees and biclusters are useful tools in the elucidation of existing relationship patterns between the community of dipterans collected.